Peranan PT. BTPN Syariah Tbk dalam Pembangunan Ekonomi Berkelanjutan: Studi Kasus pada Pelaku UMKM di Pasuruan - Novelika, Lutfiyah Rahma; Ridlwan, Ahmad Ajib (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research examines the role of BTPN Syariah in supporting Micro, Small and Medium Enterprises (MSMEs) in Pasuruan Regency to promote sustainable economic development. The research focuses on BTPN Syariah's contribution in providing sharia financing products and empowerment programs for MSME customers. Using a qualitative approach, this research explores how the sharia financing scheme and entrepreneurship training organized by BTPN Syariah help MSMEs overcome capital limitations and improve their business skills. This research uses a descriptive qualitative method, with secondary data collection (articles, statistical data, and books), and primary data with direct interviews. The results show that BTPN Syariah's mentoring and strategic partnership programs significantly strengthen the MSME sector, improve their competitiveness, and promote financial inclusion in Pasuruan. The approach applied by BTPN Syariah focuses not only on increasing profits but also on social welfare and inclusiveness, making it one of the important pillars in realizing sustainable economic development in the area.